Mutations in SELENBP1, encoding a novel human methanethiol oxidase, cause extraoral halitosis. (January 2018) - Pol, Arjan; Renkema, G.; Tangerman, Albert; Winkel, Edwin; Engelke, Udo; de Brouwer, Arjan; Lloyd, Kent; Araiza, Renee; van den Heuvel, Lambert; Omran, Heymut; Olbrich, Heike; Oude Elberink, Marijn; et al.
Abstract Selenium-binding protein 1 (SELENBP1) has been associated with several cancers, although its exact role is unknown. We show that SELENBP1 is a methanethiol oxidase (MTO), related to the MTO in methylotrophic bacteria, that converts methanethiol to H2 O2, formaldehyde, and H2 S, an activity not previously known to exist in humans. We identified mutations inSELENBP1 in five patients with cabbage-like breath odor. The malodor was attributable to high levels of methanethiol and dimethylsulfide, the main odorous compounds in their breath. Elevated urinary excretion of dimethylsulfoxide was associated with MTO deficiency. Patient fibroblasts had low SELENBP1 protein levels and were deficient in MTO enzymatic activity; these effects were reversed by lentivirus-mediated expression of wild-typeSELENBP1 .Selenbp1 -knockout mice showed biochemical characteristics similar to those in humans. Our data reveal a potentially frequent inborn error of metabolism that results from MTO deficiency and leads to a malodor syndrome. Ron Wevers and colleagues report that mutations in the methanethiol oxidase geneSELENBP1 cause chronic extraoral halitosis. They find that enzyme deficiency leads to increased levels of methanethiol and dimethylsulfide in the breath and that knockout mice have similar biochemical phenotypes.